2013
DOI: 10.1158/2159-8290.cd-13-0202
|View full text |Cite
|
Sign up to set email alerts
|

ceRNA Cross-Talk in Cancer: When ce-bling Rivalries Go Awry

Abstract: The cancer transcriptome is characterized by aberrant expression of both protein-coding and non-coding transcripts. Similar to mRNAs, a significant portion of the non-coding transcriptome including long non-coding RNAs and pseudogenes harbors microRNA-response elements. The recent discovery of competitive endogenous RNAs (ceRNA), natural decoys that compete for a common pool of microRNAs, provides a framework to systematically functionalize MRE-harboring non-coding RNAs and integrate them with the protein-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
616
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(646 citation statements)
references
References 58 publications
6
616
2
Order By: Relevance
“…Nevertheless, emerging evidence shows that some lncRNAs may partake in the ceRNA regulatory circuitry. [36][37][38] Han et al 39 showed that MALAT1 mediates serum response factor by competing for miR-133 in myogenesis, which implies that MALAT1 can act as a ceRNA. Our results indicated that the direct binding ability of the miR-101b on the MALALT1 transcript, in line with the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, emerging evidence shows that some lncRNAs may partake in the ceRNA regulatory circuitry. [36][37][38] Han et al 39 showed that MALAT1 mediates serum response factor by competing for miR-133 in myogenesis, which implies that MALAT1 can act as a ceRNA. Our results indicated that the direct binding ability of the miR-101b on the MALALT1 transcript, in line with the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies revealed that ceRNAs could serve as post-transcriptional regulators of protein-coding gene expression by decoying miRNAs from other target transcripts, such as lncRNAs, mRNAs, pseudogenes and circRNAs [21,22]. In this study, based on the high-throughput RNAsequencing data, we constructed putative ceRNA networks by integrating lncRNAs, circRNAs, mRNAs and miRNAs in the endometrium of dairy goats.…”
Section: Discussion Cerna Network In the Endometrium Of Dairy Goatsmentioning
confidence: 99%
“…In The Cancer Genome Atlas human lung adenocarcinoma database (https://gdc.cancer.gov/) (n = 1,016 tumors), ZEB1 and ITGA1 mRNA levels were positively correlated (Supplemental Figure 4B). In 344SQ cells, ITGA1 and miR181b were approximately equimolar (~300 copies per cell) (Figure 3B), an important determinant of ceRNA functionality (21). ITGA1 contains 3 predicted miR-181b-binding sites in the coding sequence and 1 site in the 3′-untranslated region (3′-UTR) (www.…”
Section: Resultsmentioning
confidence: 99%